Centering Ability of ProTaper Next and WaveOne Classic in J-Shape Simulated Root Canals - Troiano, Giuseppe (ScientificWorldJournal, 2016)
Introduction. The aim of this study was to evaluate and compare the shaping and centering ability of ProTaper Next (PTN; Dentsply Maillefer, Ballaigues, Switzerland) and WaveOne Classic systems (Dentsply Maillefer) in simulated root canals. Methods. Forty J-shaped canals in resin blocks were assigned to two groups (n = 20 for each group). Photographic method was used to record pre- and postinstrumentation images. After superimposition, centering and shaping ability were recorded at 9 different levels from the apex using the software Autocad 2013 (Autodesk Inc., San Rafael, USA). Results. Shaping procedures with ProTaper Next resulted in a lower amount of resin removed at each reference point level. In addition, the pattern of centering ability improved after the use of ProTaper Next in 8 of 9 measurement points. Conclusions. Within the limitations of this study, shaping procedures with ProTaper Next instruments demonstrated a lower amount of resin removed and a better centering ability than WaveOne Classic system.